1779 R.I. Laws, Oct. Reg. Sess. 32 - (:unkn) unknown (My University, 1779)
"[E]ach and every effective Man as aforesaid [had to] provide, and at all times be furnished, at his own Expence (excepting such Persons as the Town-Councils of the Towns in which they respectively dwell or reside shall adjudge unable to purchase the same) with one good Musquet, and a Bayonet fitted thereto, with a Sheath and Belt, or Strap, for the same, one Ram-rod, Worm, Priming-wire and Brush, and one Cartouch-Box."
Keywords: MILITIAS; REQUIRED POSSESSION